2016
DOI: 10.21608/jpp.2016.46810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano-Fertilizer (Lithovit) and Potassium on Leaves Chemical Composition of Egyptian Cotton Under Different Planting Dates.

Abstract: Two field experiments were carried out at El-Gemmeiza Agricultural Research Station, El-Gharbia Governorate in 2014 and 2015 seasons, to study the effect of nano-fertilizer (Lithovit) rates (0, 2.5, 5 and 7.5 g/l) and foliar potassium fertilizer (in the form of Potasin-P) rates (2.5, 5 and 7.5 cm 3 /l) under three planting dates (8 April, 8 May and 8 June) on leaves chemical composition of the Egyptian cotton (Gossypium barbadense L.), cultivar Giza 86. Cotton plants were foliar sprayed with Lithovit and Potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…The recorded increase in reducing sugars, sucrose and starch in stressed plants treated with lithovit spray is analogous to the results of Abo-Sedera et al (2010), which may be due to that lithovit contains Mg, the prosthetic group of chlorophyll molecules and it is essential for the metabolism of carbohydrates, where it facilitates their translocation (Abo-Sedera et al, 2016;Attia et al, 2016). In addition, it contains P, as pyridoxal, is essential for the biosynthesis of chlorophyll and is also involved in the biosynthesis of phosphoglycric acid which plays an important role in CO 2 conversion to sugar; i.e.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The recorded increase in reducing sugars, sucrose and starch in stressed plants treated with lithovit spray is analogous to the results of Abo-Sedera et al (2010), which may be due to that lithovit contains Mg, the prosthetic group of chlorophyll molecules and it is essential for the metabolism of carbohydrates, where it facilitates their translocation (Abo-Sedera et al, 2016;Attia et al, 2016). In addition, it contains P, as pyridoxal, is essential for the biosynthesis of chlorophyll and is also involved in the biosynthesis of phosphoglycric acid which plays an important role in CO 2 conversion to sugar; i.e.…”
Section: Discussionsupporting
confidence: 82%
“…This increase may be because it is taken up directly through the stomata and is converted into carbon dioxide leading to enhanced photosynthetic efficacy (Carmen et al, 2014). Lithovit contains an amount of micro-and macronutrients, like Mg and Fe; where Mg rapidly penetrates the leaves and plays an important role in chlorophyll biosynthesis and in the number of chloroplasts/cell which significantly increases the concentration of photosynthetic pigments (Attia et al, 2016). Moreover, Fe plays an important role in photosynthetic reactions, activates several enzymes and improves the performance of photosystems (Sheykhbaglou et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, untreated plants scored the highest values of peroxidase, phenoloxidase and proline compared with those obtained from JA and Li combination rates. Similar results were obtained by Attia et al (2016).…”
Section: Chemical Compositionssupporting
confidence: 90%
“…Huang et al (2017) mentioned that JA have functions in a remarkable number of plant developmental events, including primary root growth and reproductive development. Moreover, Hamoda et al (2016) found that application of lithovit caused significant increases in plant growth parameters.…”
Section: Growth Charactersmentioning
confidence: 99%